IMPLEMENTATION OF GEOGEBRA HELP INKUIRI METHOD TO INCREASE ABILITY OF MATHEMATICAL PROBLEMS CLASS STUDENTS XI-TEI B SMK IT DEVELOPMENT OF CIMAHI CITY ON MATERIALS RULES OF SINUS AND COSINUS - Dena Handriana; Rosalina Rolina; Asep Mulyana (Kopertis Region IV Jabar and Banten, 2018)
This research is an action research study . The problem formulated in this research is whether through geographical assisted inquiry method , mathematical problem solving ability of students of class XI-TEI B SMK TI Development on the material of sinus and cosine rules can be improved? The aim is to examine the improvement of problem solving ability of students of class XI-TEI B SMK IT Development of Cimahi through geogebra assisted inquiry method .This research was conducted on the students of class XI-TEI B SMK IT Development Cimahi academic year 2017-2018 with the number of students 24 people. The instrument used is a test of learning outcomes as a test of students' mathematical problem solving abilities of the sin and cosine rules, cycle I , II and II tests (after giving of action) and observation sheet for teachers and students for the conditions of action implementation. R prosedu study consisted of: (1) planning, (2) p elaksanaa n action, (3) observation and evaluation, and (4) r efleksi. The average value of the results of the test cycle II, which is 30 , 25 increased by 16.17 compared to the average value of the results of the test cycle I, namely 14.08. And the average value of the third cycle test results that is 76 , 75 increased by 46.50. Based on the performance indicators, it is concluded that the mathematical problem solving ability of students of class XI-TEI B SMK TI Pembangunan Cimahi on the material of sinus and cosine rules can be improved through geogebra assisted inquiry method .